SmartNotes Encrypted with Hybrid Cryptography Combining Rivest Cipher 4 and XChaCha20 - Elizabeth Piscelia Kusuma; Aqeela Nashwa Naysilla; Bagas Dwi Yulianto (Fakultas Teknik Universitas Bhayangkara, 2025)
Digital note-taking applications serve as essential tools for personal information management, presenting opportunities for enhanced security mechanisms to protect sensitive data. Most current solutions depend on server-side processing, creating potential vulnerabilities and privacy concerns. However, a robust solution that fully executes hybrid encryption on the client-side to seamlessly protect both text and image data within a single application remains unexplored. This study introduces SmartNotes, a web-based application safeguarding text and image notes through an innovative hybrid encryption system synergistically combining RC4 and XChaCha20 algorithms. A key contribution is the full client-side execution of encryption–decryption processes, eliminating server dependencies and significantly reinforcing data confidentiality. The hybrid design strategically utilizes RC4 for rapid data processing and XChaCha20 for robust cryptographic protection, creating an optimal balance between performance and security. System performance was rigorously evaluated using seven private datasets under diverse key conditions. Testing methodology included comprehensive assessment of processing speed, data integrity verification, and resistance against unauthorized access attempts. Results demonstrated flawless data restoration across all test cases, validating robustness and reliability. Encryption averaged 1.5 seconds, while decryption required 20.20 seconds metrics well-suited for practical web environments. These findings affirm SmartNotes delivers a secure, autonomous, user-centric solution for digital note management, advancing applied cryptography through a novel client-side hybrid encryption paradigm. This approach successfully balances strong security with practical performance, making it suitable for securing data in everyday web applications.